Tattoos: Art, Symbol, and History in Dayak Salako - Cornelius Kiki Hartanto; Donatianus BSE. Praptantya; Diaz Restu Darmawan; Ita Lusia; Devi Fridayanti (Institut Seni Indonesia Denpasar, 2023)
It is the product of qualitative research with a phenomenon approach that covers several stages of observation, deep interview, and documentation. This qualitative work is done in the large Sajingan district, Sambas. The research discussed the phenomenon of tattooing the Dayak Salako people. In the Dayak, tattoos get important attention inside, where the value and meaning behind the tattoo motif adorns the body of the Dayak. The tattoo on the dayak has a long history. Especially the traditional tattoo that is commonly known to the dayak people as the flower of eggplant, it is one of the tattoos in dayak Iban. In Dayak Salako's own well-known tattoos are a form of transcultural interaction with other hackers who have tattoos. Views have also been given to tattoos in which the study includes two types of tattoos found in the Dayak Salako, it has a traditional motif and contemporary tattoos. With the development and progress of knowledge technology regarding tattoos and tattoo meanings transferred to a new meaning to the use of tattoos among the Dayak Salako people. New tattoo motifs emerged that included artistic value, meaning, and viewpoint. The essence of the tattoos used by the dayak Salako people has become an interesting issue because of their many interfaces with the Dayak Iban and their tattoos add to their knowledge of the tattoo.